THE PROSPECTS OF OIL AND GAS CONTENT OF THE SINIAN SYSTEM OF THE SICHUAN BASIN OF CHINA - Pribilova, V. N.; Chunsian, Khou (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
In the article an evaluation of the prospects of oil and gas content of the Sinian system of the Sichuan Basin is given. Two large sedimentary basins in China – the Sichuan Basin in the south and the Tarim Basin in the west are of particular interest. These two basins which include thick mass of shale rich in organic substances cover vast areas and have good reservoir properties for development. An analysis of the importance of previous researches regarding the prospects of this territory with respect to oil and gas content was carried out. In recent years a comprehensive analysis of facies sediments of the Sinian system, the oil-source rock and an analysis of the conditions of the accumulation of oil and gas were conducted in this respect. Consequently, four favourable exploratory promising areas were chosen in an optimal way, including the area of the paleoledge Leshan-Lunnyuisy which is a favourable promising exploratory area of the Sinian system of the Sichuan Basin. As a result of an analysis of the oil and gas content of the Sichuan Basin it was determined that 3 large paleoledges are being developed there: the paleoledge Leshan-Lunnyuisy of the Caledonian period, the paleoledge Luzhou of the Indo-Chinese period and the paleoledge Kaijiang of the Indo-Chinese period. These 3 paleoledges are of great importance for the oil and gas accumulation in the Sichuan Basin. In 90% of areas in the central part of the basin mainly limited platform facies represented by subfacies of internal platform banks and subfacies of dolomitic plateaus are developed. As a result of the research it was determined that the Sinian system of the Sichuan Basin has the main basic conditions for the formation of large gas fields. A large hereditary paleoledge ensures the conditions for the formation and accumulation of oil and gas of the Sinian system. Persistent sediments in the area laid a foundation for large-scale development of the structure of reservoirs and cap rock and also the oil-source rock.